Identification of endolithic traces on stone monuments and natural outcrops: preliminary evidences1. (30th May 2014) - Casanova Municchia, A.; Caneva, G.; Ricci, M. A.; Sodo, A.; Ropret, Polonca; Madariaga, Juan Manuel
<x xml:space="preserve">Abstract</x> Four different lithotypes of rock gathered from stone monuments and natural outcrops in Temperate and Mediterranean bioclimates, with endolithic microorganism colonization (cyanobacteria, fungi, and lichens), have been analysed by Raman spectroscopy. Endolithic microorganisms can penetrate actively into the rocks giving rise to biodeterioration phenomena. Often the biological origin of these deterioration phenomena is not recognized and confused with abiotic damages. The aim of this work is to identify by Raman spectroscopy the endolithic traces on stones, due to current or past biological colonization. The Raman spectra show the presence of bio‐markers characteristic of the strategy adopted by microorganisms against strong UV‐radiation and dry conditions, such as scytonemin, anthraquinone compounds, and carotenoids. Moreover, we have identified different geo‐markers such as goethite and lepidocrocite because of the mobilization of iron by lichen metabolic activity. Importantly, we have identified for the first time by Raman spectroscopy, traces of endolithic microorganisms on stone monuments located in Temperate and Mediterranean bioclimate, where extreme climate conditions are not foreseen. Copyright © 2014 John Wiley & Sons, Ltd.